What Inspires Leisure Time Invention? - Lee N. Davis; Jerome Davis; Karin Hoisl (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2009)
This paper seeks to understand the intriguing but only sparsely explored phenomenon of “leisure time invention,” where the main underlying idea for the new product or process occurs when the inventor is away from the workplace. We add to previous research by focussing on the inventive creativity of the individual researcher, and reassessing the image of researchers inventing during unpaid time – who have often been dispatched as “hobbyists”. Based on the responses from a survey of over 3,000 German inventors, we tested hypotheses on the conditions under which leisure time invention is likely to arise. Results suggest that the incidence of leisure time invention is positively related to exposure to a variety of knowledge inputs – but, surprisingly, not to the quality of prior inventive output. Leisure time inventions are more frequently observed in conceptual-based technologies than in science-based technologies, in smaller R&D projects, and in externally financed R&D projects.
urn:nbn:de:bvb:19-epub-10457-2
Keywords: O31; O32; O34; J22; 650; Leisure Time; Inventiveness; Organizational Creativity; Innovation; Kreativität; Erfindung; Freizeit; Verhalten